Physiological and subjective differences between walking in flat soled shoes versus fitness shoes - Tepper, Stephanie (My University, 2010)
The purpose of this study was to determine if MBT, Skechers Shape-Ups, or Reebok's EasyTone shoes provide walkers with a more intense workout than New Balance walking shoes. Subjects included 12 physically active women ranging from 19 to 24 years of age. Each subject completed 12, 5-minute exercise bouts. The exercise bouts were completed while wearing the four different types of shoes at three different workloads: 3.0 mph/0% grade, 3.5 mph/0% grade, and 3.5 mph/5.0% grade. There was no significant difference in RPE, VO2, HR, or caloric expenditure between shoe conditions. The results of his study indicate that there is no evidence that fitness shoes provide users with a more intense workout than regular walking shoes.
Keywords: Walking -- Physiological aspects; Women's shoes